2017
DOI: 10.1111/jvh.12680
|View full text |Cite
|
Sign up to set email alerts
|

Serum lincRNA‐p21 as a potential biomarker of liver fibrosis in chronic hepatitis B patients

Abstract: Serum long non-coding RNAs (lncRNAs) are emerging as promising biomarkers for various human diseases. The aim of this study was to investigate the feasibility of using serum long intergenic non-coding RNA-p21 (lincRNA-p21) as a biomarker for chronic hepatitis B patients. Serum lincRNA-p21 levels were quantified using real-time PCR in 417 CHB patients and 363 healthy controls. The promoter methylation level of lincRNA-p21 was detected using bisulphite-sequencing analysis in primary hepatic stellate cells (HSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 38 publications
(43 reference statements)
0
37
0
Order By: Relevance
“…Serum levels of lncRNA-p21 were negatively correlated with liver fibrosis in HBV patients [117]. Yu et al [68] determined that lncRNA-p21 enhanced the expression of PTEN by sequestering miR-181b as a ceRNA and inhibited HSC activation through the PTEN/Akt pathway in liver fibrosis [68].…”
Section: Lncrnap21mentioning
confidence: 99%
“…Serum levels of lncRNA-p21 were negatively correlated with liver fibrosis in HBV patients [117]. Yu et al [68] determined that lncRNA-p21 enhanced the expression of PTEN by sequestering miR-181b as a ceRNA and inhibited HSC activation through the PTEN/Akt pathway in liver fibrosis [68].…”
Section: Lncrnap21mentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are non-protein-coding RNAs that lack an open reading frame [5]. Recently, studies have found that lncRNAs are involved in various cellular functions through different mechanisms such as posttranscriptional, transcriptional [6][7][8]. Zhang et al revealed that lncRNA LINC00305 promotes inflammation through activation of the aryl hydrocarbon receptor repressor (AHRR)-nuclear factor nuclear factor-kB (NF-κB) pathway [9].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs induced by HCV infection may regulate the expression of coding genes required for the replication of the virus or regulation of genes involved in the cellular antiviral response 33 . The expression levels of the lncRNA maternally expressed gene 3 (MEG3) 34 and the lincRNA p21 35 have been found to be reduced during liver fibrosis and, thus, may potentially serve as biomarkers of fibrosis. The lncRNA growth arrest-specific transcript 5 (GAS5) inhibits HCV replication 36 and participates in the activation and proliferation of HSCs 37 .…”
Section: Discussionmentioning
confidence: 99%